Variety of Anopheles mosquito in Salamwates Village, Dongko Subdistrict Trenggalek District, East Java Province (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2019)
Malaria is an infectious disease caused by parasites from the genus Plasmodium and transmitted through the bites of Anopheles mosquitoes. This study was an observational analytic research by using adult mosquito specimens. The mosquitoes were caught using indoor net trapping and outdoor cow baited net trapping started at 18.45 to 24.00 for six catching times. Outdoor cow baited net trapping caught 61 mosquitoes from seven different species namely An. aconitus, An. annularis, An. barbirostris, An. indefinitus, An. kochi, and An. vagus. Human bait trap only trapped one species, An. indefinites. The most often caught mosquito was a zoophilic An. barbirostris, while An. indefinitus was the only spesies of anthropozoophilic mosquito and suspected as the malaria vector because they were caught using indoor human bait trap.